2022
DOI: 10.46507/jcgpp.v3i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Actor Collaboration in Improving the Economy of the Fishing Community in Karangantu Coastal Area of Serang, Indonesia

Abstract: The fishing community is a community that is strongly dependent on the sustainability of marine natural resources. Indonesia is the largest archipelagic country in the world and has a wealth of marine economic potential. Karangantu Coastal Area, Serang City is located on Banten’s North Coast which has a fairly good marine potential and has a National Fishing Port (PPN) which is a type B fishing port in Banten Province. These advantages were why PPN Karangantu was appointed as a fisheries industrial area (forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Therefore, the control object in this study consists of socio-economic subsystems which are characterized by the heterogeneity of their development in each region. Maulana and Yulianti (2022), in examining the problems of fishing in the Karangantu coastal region in Serang (Indonesia), found that multi-stakeholder cooperation has a positive impact on the development of the industry. At the same time, the role of local authorities was defined as being among the most important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the control object in this study consists of socio-economic subsystems which are characterized by the heterogeneity of their development in each region. Maulana and Yulianti (2022), in examining the problems of fishing in the Karangantu coastal region in Serang (Indonesia), found that multi-stakeholder cooperation has a positive impact on the development of the industry. At the same time, the role of local authorities was defined as being among the most important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The starting situation is a crucial determinant of the level of trust, conflict, and social capital available for collaboration. It is comprised of three subcomponents: imbalances in power, resources, and knowledge; the motivations of stakeholders to collaborate, which are dependent on their expectations for the partnership outcome; and the history of conflict or previous collaborations (Ansell & Gash, 2008;Emerson et al, 2011;Rubio-Valera et al, 2012;Ran & Qi, 2017;Morley & Cashell, 2017 al., 2012;Maulana & Yulianti, 2022). Leadership plays a vital role in guiding the collaborative process and promoting consensus.…”
Section: Collaborative Governancementioning
confidence: 99%
“…Dalam mengidentifikasi aktor yang terlibat dalam kebijakan pengembangan pariwisata di Provinsi Banten, maka perlu melakukan analisis aktor. Menurut Ondee dan Pannarunothai (Anderson, 2003;Bryson et al, 2011;Lawrence, 2017;Maulana & Yulianti, 2022;Ondee & Pannarunothai, 2008;Rafika et al, 2016;Yuningsih et al, 2019) analisis aktor adalah metode sistematis untuk mengumpulkan dan menganalisis sebuah data dari kepentingan aktor (individu, kelompok dan organisasi) dalam rangka mengidentifikasi aktor-aktor yang terlibat dalam kebijakan ini, baik aktor utama dalam sebuah sistem pengelolaan, menilai kepentingan dari beberapa aktor masing-masing (pertaruhan), serta memprediksi potensi yang berpengaruh pada formulasi kebijakan pegembangan pariwisata di Provinsi Banten. Sebab secara konseptual pariwisata adalah industri yang multidimensi dan lintas sektoral.…”
Section: Provinsi Bantenunclassified